HUBUNGAN ANTARA DUKUNGAN SOSIAL KELUARGA DENGAN PSYCHOLOGICAL WELL-BEING PADA PEKERJA SEKS KOMERSIAL DI PANTI REHABILITASI - Welhelmina Maria Yuniaputry Hailitik; Maggareta Erna Setianingrum (Jurnal Psikohumanika, 2019)
Abstract The research aims to knowing the relationship between social support and psychological well-being in commercial sex worker. This research is designed by using sampling saturated technique with 55 participants. Variable of family social support using Cutrona's theory (1987) which consists of 24 items and psychological well-being variable using Ryff's theory (1989) which consists of 42 items. The research method in data collection using the scale method, that is the scale of family social support and the ryff’s psychological well-being scale. Data analysis using the product moment correlation analysis techniques and obtained a comparison coefficient of 0.290 with a sig value. = 0,000 (p <0.001). Based on the research results shows a positive relationship between family social support and psychological well-being on commercial workers in rehabilitation home.